A novel method for determining the X-ray beam angulation of the supraspinatus outlet view. (November 2022) - Zheng, Xiaoli; Hu, Jingying; Xu, Jian; Wang, Zhen; Shu, Zhenyu; Gong, Xiangyang
Background: Rapid and accurate quantification of the supraspinatus outlet view (SOV) is a clinical challenge. Purpose: To quantify the X-ray beam angle of the SOV using the horizontal angle of the subscapular spine line (SSSL) and to further verify the feasibility of this method. Material and Methods: A total of 119 patients who underwent shoulder computed tomography (CT) examination were enrolled in the retrospective study. Three-dimensional (3D) CT reconstruction was performed and manually adjusted to provide the position similar to SOV. The rotation angle of the 3D image along the long axis of the human body (marked as β) was obtained. The horizontal angle of SSSL (marked as α) was measured on the anteroposterior localizer image of shoulder CT. Pearson correlation and linear regression correlation analysis were performed. In addition, the first-time success rate between the experience-based group and the measurement-based group were compared to verify the novel method. Results: We found a linear correlation between α and β (r = 0.962; P  = 0.000). There was no significant correlation between the experience-based group and the measurement-based group in terms of age ( P  = 0.500), sex ( P  = 0.397), and side ( P  = 0.710), but there was a significant statistical difference in the first success rate between the two validation groups (χ 2  = 5.808 a, P  = 0.016). Conclusion: This novel quantitative measurement method for determining the X-ray beam angle of SOV using the horizontal angle of SSSL is feasible.